Strategic Library Management for Health Information Literacy to Support SDG 3 : A Literature Review - Mohi, Salsabillah; Zulaikha, Sri Rohyanti; Afrina, Cut (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Global health and well-being issues in SDGs 3 require libraries to play an active role as mediators of health information. The purpose of this study is to analyze the urgency of Information Literacy as a key instrument for achieving SDGs 3 and to formulate the strategic role of library management in ensuring that Information Literacy programs are aligned with and contribute directly to the Health and Well-being targets set out in the SDGs. Research Method uses a systematic literature review method, data were sourced from Google Scholar, Scopus, Web of Science, and Dimensions for the period 2015-2025. Following a rigorous selection process, 36 articles were analyzed using systematic content analysis techniques. Data Analysis is carried out using systematic content analysis techniques to classify and synthesize literature into coherent research findings. Results  The findings reveal that strategic library management through policy integration, ICT digitization, and facility strengthening plays a crucial role in enhancing health information literacy. Librarians act as facilitators bridging information gaps via collaboration with health institutions. These strategic partnerships ensure literacy programs remain relevant, inclusive, and capable of addressing resource constraints. In Conclusion, that integrated library management is essential for improving evidence-based health decision-making in communities, thereby contributing significantly to the attainment of SDG 3 targets. Keywords : Information Literacy, Library Management, SDGs 3